Design Method of Engine Timing Chain System - Yin Debing; Weng Jianliang; Qian Jiang; Zhao Jianxiang (Jixie chuandong)
The development process of engine timing system and the calculation method of timing chain tension are studied. The key technical points of main parts including timing chain,guide rail and tensioner are presented when designing the overall layout of engine timing system. According to the simulation analysis of designed engine timing chain system is carried out,the structures and load conditions of each component is improved to reach a better power transmission. Consequently,the requirements of high performance and low noise of the engine is satisfied. From the results of this study,it is concluded that this development process is reasonable and practical.